Simulation of Proton Beam Effects in Thin Insulating Films - Ljubinko Timotijevic; Irfan Fetahovic; Djordje Lazarevic; Milos Vujisic (International Journal of Photoenergy)
Effects of exposing several insulators, commonly used for various purposes in integrated circuits, to beams of protons have been investigated. Materials considered include silicon dioxide, silicon nitride, aluminium nitride, alumina, and polycarbonate (Lexan). The passage of proton beams through ultrathin layers of these materials has been modeled by Monte Carlo simulations of particle transport. Parameters that have been varied in simulations include proton energy and insulating layer thickness. Materials are compared according to both ionizing and nonionizing effects produced by the passage of protons.